Learning English Vocabulary Through the Duolingo Application to Help Young Learners’ Reading Skill - Geral Pratasik (English Education Postgraduate Program, Universitas Negeri Manado, 2022)
This study aims at finding out whether the Duolingo application can be used in learning vocabulary to help young learners in their reading skills. Mastery of English is something that is important nowadays. To be able to master English, it is necessary to master the components in it, one of the components is vocabulary, and vocabulary is also very helpful in English skills, including reading skills. In learning English vocabulary, it will be easier if it is done from an early age, or in a critical period. In this modern world, there are many ways that young learners can use to learn vocabulary, one of which is using the Duolingo application. Dulingo is an interesting app that makes it suitable for young learners. At the end, the results of this research will be seen.